Celiac Disease Among Preschool Children: A Retrospective Analysis - Acar, Ufuk; Deveci, Uğur (Harran University, 2023)
Background: The aim of this study is to evaluate the medical parameters of celiac disease cases in the preschool age group in terms of public health and to make recommendations to health professionals, policy makers and the society. Materials and Methods: This study was conducted between February 2017 and December 2018 in Şanlıurfa Education and Research Hospital, Pediatric Gastroenterology Clinic. Clinical and laboratory findings of preschool children diagnosed with celiac disease were retrospectively analyzed. Anamnesis, physical examination findings, laboratory findings, endoscopic biopsies and pathology results of pati-ents were evaluated. Results: The most common presenting complaint was growth retardation (96.3%), followed by chronic diarrhea (32.5%) and constipation (27.5%). Height-for-age and weight-for-age values were found to be lower in patients with chronic diarrhea and duodenitis compared to those without (p<0.05). Patients with strong positive tissue transglutaminase-IgA (tTG IgA) levels had significantly higher Marsh scores (p<0.05). Conclusions: For preschool-age children, initiating the diet via early diagnosis and ensuring adherence to diet are the main objectives. Children adhering to the diet have a higher success in elementary school and a shorter adaptation period.

Amaç: Bu çalışmanın amacı, okul öncesi yaş grubundaki çölyak hastalığı vakalarının tıbbi parametrele-rini halk sağlığı açısından değerlendirmek ve sağlık profesyonellerine, politika yapıcılara ve topluma önerilerde bulunmaktır. Materyal ve Metod: Bu çalışma Şubat 2017-Aralık 2018 tarihleri arasında Şanlıurfa Eğitim ve Araştırma Hastanesi Çocuk Gastroenteroloji Kliniği'nde yapıldı. Çölyak hastalığı tanısı konan okul öncesi çocukların klinik ve laboratuvar bulguları geriye dönük olarak incelendi. Hastaların anamnezleri, fizik muayene bulguları, laboratuvar bulguları, endoskopik biyopsileri ve patoloji sonuçları değerlendirildi. Bulgular: En sık başvuru şikayeti gelişme geriliği (%96.3) olup, bunu kronik ishal (%32.5) ve kabızlık (%27.5) izlemektedir. Kronik ishali ve duodeniti olanlarda, olmayanlara göre yaşa göre boy ve yaşa göre ağırlık değerleri daha düşük bulunmuştur (p<0.05). Güçlü pozitif doku transglutaminaz-IgA (tTG IgA) düzeylerine sahip hastaların Marsh skorları anlamlı olarak daha yüksek tespit edilmiştir (p<0.05). Sonuç: Okul öncesi çağındaki çocuklarda erken tanı ile diyete başlanması ve diyete uyumun sağlanması temel hedeflerdir. Diyete bağlı kalan çocukların ilkokulda başarıları daha yüksek ve uyum süreleri daha kısadır.
Okul Öncesi Çocuklarda Çölyak Hastalığı: Retrospektif Bir Analiz
Keywords: Pediatric Gastroenterology; Çocuk Gastroenterolojisi; Clinical Sciences (Other); Klinik Tıp Bilimleri (Diğer)